ANALYSIS AND REFORM THE TRANSPORT SECTOR UKRAINE (Transport systems and technologies, 2018)
The article analyzes the development of the transport system of Ukraine, defined the main problems of the transport sector, transport integration of Ukraine into the European and global transport networks. Directions for further reform of the transport sector in Ukraine.The object of study – the transport system of Ukraine. Purpose – to solve common problems in the development of transport infrastructure, analysis of problems and prospects of development of international transport in Ukraine. Method study – statistical analysis of the main indicators of transport modes Ukraine. Transport sector of Ukraine is a considerable and important segment for the economy of country, in fact effective and concerted work of a whole transport system is movable force for general development of countr . However, existent competition at the market of transport services, all requires the new going near development of transport relations, creation of NT and upgrading of services. Conducting the global analysis of work of all types of transport it is possible to assert that development of a transport infrastructure is the key element of development of all economy of country. To a transport system made great demand in relation to quality, regularity and reliability of transport connections, maintenance of loads, safety of carrying passengers, speed and quality of delivery. A requirement is in a transport system that functions clearly, all increases, becomes the base of steady development of productive forces of regions, and also mortgage of integration of our country to the world markets. The events of improvement of a transport system of country offer in this research. The special attention is spared to the problems of transport transportations and development of recommendation in relation to the prospects of their further functioning. Front-rank transport technologies, and factors that influence on development of a transport system, are considered.
Keywords: transportation system, freight, transit, international transport, transportation technology, logistics system, clusters, transportation corridors